2016
DOI: 10.3389/fpsyg.2016.01499
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Restraint Partially Mediates the Relationship between Impulsivity and Binge Eating Only in Lean Individuals: The Importance of Accounting for Body Mass in Studies of Restraint

Abstract: Binge eating is characteristic of eating and weight-related disorders such as binge eating disorder, bulimia nervosa, and obesity. In light of data suggest impulsivity is associated with overeating specifically in restrained eaters, this study sought to elucidate the exact nature of the associations between these variables, hypothesizing that the relationship between impulsivity and binge eating is mediated by restrained eating. We further hypothesized that the role of dietary restraint as a mediator would be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
(40 reference statements)
1
8
0
1
Order By: Relevance
“…However, this behavior is not clearly associated with reduced body weight. While some studies suggest that restraint may be a useful strategy in controlling body weight ( van Strien et al, 2012 ; Girz et al, 2013 ; Schaumberg et al, 2016 ), others report that excessive restriction may have a counterproductive effect and may instead lead to overeating, binge eating, weight gain and the development of eating disorders in both genders ( Herman and Polivy, 1980 ; Snoek et al, 2008 ; Masuda et al, 2015 ; Coffino et al, 2016 ; Walther and Hilbert, 2016 ). Lowe et al (2013) concluded that, in most cases, restrained eating did not predict weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…However, this behavior is not clearly associated with reduced body weight. While some studies suggest that restraint may be a useful strategy in controlling body weight ( van Strien et al, 2012 ; Girz et al, 2013 ; Schaumberg et al, 2016 ), others report that excessive restriction may have a counterproductive effect and may instead lead to overeating, binge eating, weight gain and the development of eating disorders in both genders ( Herman and Polivy, 1980 ; Snoek et al, 2008 ; Masuda et al, 2015 ; Coffino et al, 2016 ; Walther and Hilbert, 2016 ). Lowe et al (2013) concluded that, in most cases, restrained eating did not predict weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of comparable frequency of visits to fast food restaurants and minimarts despite high availability, more restrained eating may reflect more strenuous effort to avoid high fat/sugar foods in spite of high food craving. Consistent with this interpretation, in lean undergraduates, restrained eating is a risk factor for binge-eating (Coffino et al., 2016), and restrained eating is often associated with weight gain over time (Schur et al., 2010). Weight gain in restrained eaters may be due to mood fluctuations disrupting dieting behaviors (Neimeijer et al., 2017; Polivy et al., 1994) and higher neurophysiological sensitivity to the reward value of highly palatable food (Burger and Stice, 2011; Gibson, 2006).…”
Section: Discussionmentioning
confidence: 87%
“…Cooper et al, 15 emphasize the role of certain cognitive processes in maintaining binge eating episodes in a model that categorizes a set of beliefs considered positive about the role of compulsion in reducing emotional stress (“eating helps me cope”); permissive beliefs (“it's okay to binge eat”); and negative beliefs of “no control” (“once I start eating, I can't stop”) 15 . The most cited cognitive models to explain binge eating focus on the role of cognitive restriction, or the act of dieting 6 , 14 , 16 , in addition to low self-esteem and concern with body image, shape and weight 17 19 . However, few studies evaluate the cognitive processes that contribute to the maintenance of binge eating 15 .…”
Section: Introductionmentioning
confidence: 99%